Codex Vaticanus B03 dan Codex Sinaiticus א 01 membaca secara keliru Amon sebagai Amos? - Ngoranubun, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2022)
A study of some manuscripts of Matt.1:10 shows that there are variants readings concerning the word Amon. Certain manuscript reads Amon, others read Amos, Amnon, and Ammon. The Codex Vaticanus B03 and the Codex Sinaiticus 01 א read “ΜΑΝΑCCΗ ΔΕ ΕΓΕΝΝΗCΕΝ ΤΟΝΑΜΩC”. But the Deutero-canonical Bible published by LAI and LBI read it Amon. Do theCodex Vaticaus B03 and the Codex Sinaiticus 01 א erroneusly read Amon as Amos? Throughthe stages of textual criticism, this article intends to explain that Matt. 1:10 is read erroneusly even by the Codex Vaticanus B03 and the Codex Sinaiticus א 01. And the correct reading forMatt. 1:10 is Amon and not Amos. Keywords: The Codex Vaticanus B03, The Codex Sinaiticus א 01, Amon, Amos